TLR-8, TNF-α, and ESR-1α Gene Polymorphism Susceptibility in Onset of Arthritis - Maryam Mukhtar; Nadeem Sheikh; Andleeb Batool; Tayyaba Saleem; Muhammad Babar Khawar; Mavra Irfan; Saira Kainat Suqaina (Genetics Research)
Arthritis is a genetic disorder characterized by bones and joint degradation assisted by severe pain and inflammation. It is evident by the studies that 0 candidate genes variations play vital role in its development and progression. Therefore, we investigated the genetic variation of TLR-8, TNF, and ESR-1α genes in the Pakistani population. A case-control study comprising 300 RA, 316 OA, and 412 control subjects was conducted. PCR-RFLP and direct sequencing methods were used for determining genetic variations. Analysis was performed by using PLINK and MEGA 6.0 software. Allelic and genetic frequencies of polymorphisms identified on rs3764879 (TLR-8), rs3764880 (TLR-8), rs5744080 (TLR-8), rs1800629 (TNF), rs2228480 (ESR-1α), and rs1451501590 (ESR-1α) were significantly varied among RA, OA, and controls. Novel functional mutations SCV000844945 and SCV000844946 on TLR-8 as well as a non-functional SCV000804801 and functional variation SCV000804802 on ESR-1α were also identified and reported for the first time in the studied population. Multiple site analyses indicated that polymorphisms on TLR-8 and ESR-1α genes were significant risk factors in disease onset to the next generation. In conclusion, TLR-08 and ESR-1α were significant in the onset of arthritis whereas the TNF was not found as a significant risk factor in the onset of RA and OA.